2014
DOI: 10.7314/apjcp.2014.15.4.1511
|View full text |Cite
|
Sign up to set email alerts
|

MiR-886-5p Inhibition Inhibits Growth and Induces Apoptosis of MCF7 Cells

Abstract: Background and Aims: To explore the molecular mechanisms of miR-886-5p in breast cancer., we examined roles in inhibiting growth and migration of MCF-7 cells. Methods: MiR-886-5p mimics and inhibitors were used to express or inhibit MiR-886-5p, respectively, and MTT and clone formation assays were used to determine the survival and proliferation. Hoechst 33342/ PI double staining was applied to detect apoptosis. The expression of caspase-3, caspase-8, caspase-9, MT1-MMP, VEGF-C and VEGF-D was detected by Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…Indeed, snc886-3p enrichment is above the average of the microRNAs in these experiments, indicating a specialized microRNA-like function for this small RNA product in comparison to the 5p. Although our study shows a low association of snc886-5p to AGO it does not rule out the function of snc886-5p as a microRNA, which has been shown previously in other tissues (brain [19], cervical [66,67], breast [68]). Alternatively, snc886-5p might be involved in another pathway or be a non-functional secondary product of nc886 processing.…”
Section: Discussioncontrasting
confidence: 94%
“…Indeed, snc886-3p enrichment is above the average of the microRNAs in these experiments, indicating a specialized microRNA-like function for this small RNA product in comparison to the 5p. Although our study shows a low association of snc886-5p to AGO it does not rule out the function of snc886-5p as a microRNA, which has been shown previously in other tissues (brain [19], cervical [66,67], breast [68]). Alternatively, snc886-5p might be involved in another pathway or be a non-functional secondary product of nc886 processing.…”
Section: Discussioncontrasting
confidence: 94%
“…The relative expression of proteins was determined as MMP/β-actin densitometric ratio through using TotalLab software. 8 …”
Section: Methodsmentioning
confidence: 99%
“…The levels of VEGF MMP2 and MMP9 were also reduced by reducing the expression of miR-886-5p. From results it was concluded that miR-886-5p inhibitors can be used as therapeutic agents in treatment of breast cancer as they caused a significant reduction in growth and migration of MCF-7 cells (Zhang et al, 2014).…”
Section: Mir-886-5p Inhibitorsmentioning
confidence: 99%